Systematics of the dwarf red brocket, Mazama rufina (Pucheran, 1851) (Mammalia: Artiodactyla: Cervidae), with the description of a new genus - Ramírez-Chaves, Héctor E.; Morales-Martínez, Darwin M.; Cardona-Giraldo, Alexandra; Castellanos, Oscar; Ospina, Oscar; Ossa-López, Paula A.; Rivera-Páez, Fredy A.; Noguera-Urbano, Elkin A. (Zootaxa, 2025)
The dwarf red brocket, Mazama rufina (Pucheran, 1851) is a small deer with a fragmented distribution in the montane forests of the Andes of Peru, Ecuador, Colombia, and Venezuela. Little is known about the phylogenetic relationships and the haplotype diversity of its populations, which show distribution gaps. Here we elucidate the phylogenetic relationships of M. rufina and other neotropical deer using mitochondrial data, and analyze genetic geographic variation of this taxon by using haplotype networks of the Cyt-b gene from northern South America. Our analyses recovered M. rufina as independent clade that is not part of Mazama, and sister to a clade composed of Mazama species (except Mazama chunyi) and Odocoileus. The morphometric data of cranial traits confirms that the dwarf red brocket is among the smallest species of deer in South America, only overlapping with small cis-Andean gray brockets (genus Passalites). Based on these results, we provide a new generic classification for this taxon by placing the dwarf red brocket in a new genus found only in the Andes of northern South America. The Cyt-b haplotype network of the dwarf red brocket showed a strong geographic structure caused by the interplay of Cordilleras and lowland river valleys. The genetic distances between the geographic groups were between 1.4 % (Central Cordillera of Colombia vs. Andes of Ecuador) to 2.52 % (Mérida Cordillera vs. Ecuador). The species range using Extent of Occurrence (EOO) and Area of Occupancy (AOO) was 443,764 and 796 km2, respectively, suggesting that the species could be listed as Near Threatened. However, additional information on population changes and susceptibility to habitat transformation is crucial to evaluate whether the dwarf red brocket can be deemed Vulnerable along its distribution. Compared with previous distribution hypotheses, the revised map suggests less extensive distribution gaps in Colombia and highlights priority areas for future sampling in Colombia, Ecuador, and Venezuela.